PERAN PROGRAM PERTUKARAN MAHASISWA MERDEKA DALAM MENINGKATKAN KETERAMPILAN KOMUNIKASI DAN KOLABORASI MAHASISWA PENDIDIKAN AGAMA ISLAM - Qodariah, Lailatul; Saifullah, Iman; Munawaroh, Nenden; Usman, Asep Tutun (Al’ulum Jurnal Pendidikan Islam, 2025)
This study aims to explore the role of the Merdeka Student Exchange Program (PMM) in improving the communication and collaboration skills of Islamic Education (PAI) students at Garut University. This study used a descriptive qualitative approach, data were collected through interviews and questionnaires via google form, observation, and documentation. This research was limited to 19 students of the Islamic Education Study Program who had participated in the PMM program and the Head of the Islamic Education Study Program as well as lecturers at the Faculty of Islamic Education and Teacher Training, Garut University. Data were analyzed through data reduction, data presentation in narrative form, and conclusion drawing. The results showed that the Merdeka Student Exchange (PMM) program was implemented as part of the Merdeka Learning Independent Campus (MBKM) policy to improve the quality of higher education in Indonesia, provide opportunities for students to study in different environments and broaden academic and social horizons. Through interactions with local students and activities such as group discussions, presentations, and the Nusantara Module, PAI students experienced a significant improvement in communication and collaboration skills, as well as an increase in the number of students who participated in the program.